Evaluation of the Knowledge, Attitude and Public Awareness about the Use of Antibiotics and Antibiotic Resistance in Albania - Eni Bushi1; Zehadin Gashi2 , Ledjan Malaj1,*
Antibiotic-Resistance remains a major risk to the general public's health. To assess public awareness about antibiotics usage and antibiotic resistance, survey-based research was conducted during October-December 2022 in Tirana, Albania. The aim of this research is to analyze the general public's level of knowledge and awareness of antibiotic use and resistance to antibiotics as well as to identify the demographic traits associated with them. Materials and Methods: A validated survey was used to collect the data. The survey was organized into four sections to gather information on socio-demographic traits, antibiotic use, knowledge on antibiotics, and antibiotic resistance. A Chi-square test was used to identify the associations between categorical variables. A p-value of 5% or less was considered significant for any test performed. Results: The study participants showed an overall good general knowledge of antibiotic resistance. The level of knowledge was significantly related with gender (p=0.005), education (p=0.018), and age (p<0.001). The settlement category appeared to be significantly associated with self-medication (p=0.020). Our findings imply that although individuals acknowledge the issue of antibiotic resistance, they are not fully informed about the causes and their personal role for preventing its spread. Conclusion: This research can serve as a baseline for further interventions addressing these issues and encouraging the proper use of antibiotics in the local context.